EFL Students’ Beliefs and Practices on Informal Digital English Learning Outside Classrooms - Kartilia Riayuningsih; Azhar Aziz Lubis; Dedi Sofyan (English Department - University of Sultan Ageng Tirtayasa, 2022)
Due to the ease of digital devices and internet access these days, digital learning has become a new learning environment for EFL students to study English outside their formal classrooms. This study thus aimed to find out students’ beliefs and practices on informal digital English learning outside classrooms. It involved 190 students of English Education Study Program at Universitas Bengkulu. The study was descriptive research with survey design involving quantitative and qualitative data. The quantitative data were collected via close-ended items, while the qualitative data were collected via open-ended items. The results of this study suggested that most of the students had higher levels of beliefs on informal digital English learning. Further analysis revealed the practicality, availability, flexibility, autonomy, enjoyment of digital English learning were the reasons for their beliefs. Regarding the practices, most of the students had engaged in informal digital English learning activities. However, in terms of the diversity of digital learning activities, they tended to only engage in receptive digital learning activities. Productive digital activities, particularly involving communication technology, were rarely performed. It also found a significant correlation between students’ beliefs and practices. Accordingly, comparisons with prior studies and pedagogical implications were presented.